2023
DOI: 10.3390/cells12111500
|View full text |Cite
|
Sign up to set email alerts
|

β-COP Suppresses the Surface Expression of the TREK2

Abstract: K2P channels, also known as two-pore domain K+ channels, play a crucial role in maintaining the cell membrane potential and contributing to potassium homeostasis due to their leaky nature. The TREK, or tandem of pore domains in a weak inward rectifying K+ channel (TWIK)-related K+ channel, subfamily within the K2P family consists of mechanical channels regulated by various stimuli and binding proteins. Although TREK1 and TREK2 within the TREK subfamily share many similarities, β-COP, which was previously known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Decreased expression of K2p1.1 leads to membrane depolarization and increased neuronal excitability, rendering them sensitive to mechanical and thermal stimuli. 70,71 In a study by Jia et al, it was found that systemic administration of paclitaxel resulted in a time-dependent reduction in K2p1.1 mRNA and protein expression in DRG neurons, leading to mechanical and thermal hypersensitivity in rats. Additionally, overexpression of ten-eleven translocation methylcytosine dioxygenase 1 (TET1) in DRG improved the expression of K+ channel 1.1 (K(2p)1.1) and alleviated mechanical heterotopic pain as well as heat and cold pain on the affected side in rats.…”
Section: Potassium Ion Channelsmentioning
confidence: 99%
“…Decreased expression of K2p1.1 leads to membrane depolarization and increased neuronal excitability, rendering them sensitive to mechanical and thermal stimuli. 70,71 In a study by Jia et al, it was found that systemic administration of paclitaxel resulted in a time-dependent reduction in K2p1.1 mRNA and protein expression in DRG neurons, leading to mechanical and thermal hypersensitivity in rats. Additionally, overexpression of ten-eleven translocation methylcytosine dioxygenase 1 (TET1) in DRG improved the expression of K+ channel 1.1 (K(2p)1.1) and alleviated mechanical heterotopic pain as well as heat and cold pain on the affected side in rats.…”
Section: Potassium Ion Channelsmentioning
confidence: 99%